Imágenes, trabajo y capitalismo. Sobre Trabajadores saliendo de la fábrica (Harun Farocki, 1995)=Images, labor and capitalism. On Workers Leaving the Factory (Harun Farocki, 1995) - David Montero (H-ermes: Journal of Communication, 2016)
Images, labor and capitalism. On Workers Leaving the Factory (Harun Farocki, 1995). In a specific moment of Harun Farocki’s Workers Leaving the Factory (1995), the voiceover duly notices that, since the Lumiére brothers filmed their workers in Lyon in 1896, more and more workers had actually been leaving the factory, to the point where the latter has become an empty space, turning the everyday act of leaving the Factory into a non-image. The film’s discursive stance foregrounds the factory as a hidden aspect within dominant visuality over the last century, configuring the images of workers leaving the factory as an ideological node where capitalism and visual culture collide. In fact, the sort of visual-ideological analysis carried out by Farocki in Workers Leaving the Factory widens critical practice in the field of the political economy of the image, inasmuch as it highlights its value within an exploitation system ranging from advertising to film and other culture industries. This article reflects on Farocki’s proposal with the aim of approaching the images of workers as a socio-historical reality, completely reinstated to the field of ideology and in constant conflict with a visuality focused on individuals and personal relations. From this perspective, the working class becomes invisible as a collective actor, dissolving into differences and life stories that invariably take leaving the factory as a starting point